An analysis of Idiom Using In “The Rising of The Shield Hero” - Raflis Raflis; Rafli Candra (Jurnal Ilmiah Langue and Parole, 2019)
This study aims to find out the use, contextual meaning, and types of idioms in a film titled "The Rising of the Shield Hero". An idiom is an expression that contains words, phrases or clauses that often use figurative language that is often used in communication. The meaning of an idiom is very different from the literal meaning, the idiom itself does not describe one of the words that form it. The researcher used the theory of idiom types based on Boatner and Gates and contextual meaning based on Parera. The purpose of this research; identify what types of idioms in the film, and analyze the contextual meaning in the film. This research is qualitative method, the data has been taken from the film script and analyzed. The result is indicate that idioms can be found in each forms with idiom identified in the film: there are 72 idioms in 4 forms, 52 lexemic idioms, 16 phraseological idioms, 1 frozen idiom, 3 proverbs. The most idiom are lexemic and it is hard to find frozen idioms. Finally, all of these idioms have related meanings based on the contextual meaning in the film.